Optimal Allocation of Distributed Generation in Distribution System Considering Multi-type Demand Response Resources - Nan ZHAO; Beibei WANG (Zhongguo dianli)
In recent years, the distributed generation (DG) and demand response (DR) resources have made up an increasing portion in the operation of active distribution network. In order to fully utilize the resources of distribution system, a study is made in this paper on integrated planning of intermittent distributed generation and multi-type demand response resources. To obtain the optimal allocation scheme of intermittent DG and DR, a chance-constraint programming-based bi-level optimal model is established according to their output characteristics. A series of simulations are made on the IEEE 34-node distribution system to understand the influence of DR’s interaction on DG allocation. Simulation results illustrate that DR resources can be dispatched to improve the wind curtailment, load curtailment and voltage exceeding problem, consequently enhancing the access capability of DGs. In different application scenarios such as large difference between peak and valley loads, voltage exceeding and power line congestion, the allocations of DR are also different. The model proposed in this paper lies a foundation for large-scale DR resources participating in distribution system planning.